2003
DOI: 10.1002/ejic.200200665
|View full text |Cite
|
Sign up to set email alerts
|

Photophysical and Energy‐Transfer Properties of (Salen)zinc Complexes and Supramolecular Assemblies

Abstract: The absorption, emission, and energy-transfer properties of monomeric and supramolecular (salen)Zn complexes (square and rectangular assemblies) are reported. The monomeric complexes fluoresce in solution, displaying photophysical behavior similar to typical (porphyrin)zinc complexes. Rhenium coordination chemistry is used to assemble molecular rectangles and squares that largely retain the photophysical properties of the parent compounds. Host-guest assemblies

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
50
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(59 citation statements)
references
References 18 publications
8
50
0
1
Order By: Relevance
“…Since the natural lightharvesting system contains a larger number of different chromophores, the artificial antennae require an ingenious molecular design that allows the incorporation of a number of different chromophore units and their efficient cooperation with one another, as well as acquiring light energy over a long distance to a designated unit. To mimic the antenna function, chemists have attempted to prepare different types of artificial systems [3][4][5][6][7][8][9][10] . Metallocyclophanes are of special interest since multiple chromophoric ligands can be incorporated into this system as found in photosynthetic reaction centers [8][9][10] .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since the natural lightharvesting system contains a larger number of different chromophores, the artificial antennae require an ingenious molecular design that allows the incorporation of a number of different chromophore units and their efficient cooperation with one another, as well as acquiring light energy over a long distance to a designated unit. To mimic the antenna function, chemists have attempted to prepare different types of artificial systems [3][4][5][6][7][8][9][10] . Metallocyclophanes are of special interest since multiple chromophoric ligands can be incorporated into this system as found in photosynthetic reaction centers [8][9][10] .…”
Section: Introductionmentioning
confidence: 99%
“…To mimic the antenna function, chemists have attempted to prepare different types of artificial systems [3][4][5][6][7][8][9][10] . Metallocyclophanes are of special interest since multiple chromophoric ligands can be incorporated into this system as found in photosynthetic reaction centers [8][9][10] . As for an elegant example, Wurthner and co-workers 10 demonstrated that a Pt(II)-based molecular square containing sixteen pyrene chromophores constitutes a lightharvesting system that undergoes the combination of rapid energy and efficient electron transfer processes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Not only have they played a seminal role in the development of modern coordination chemistry [2], but they can also be found at key points in the development of structural and theoretical chemistry [3][4][5][6][7], inorganic biochemistry [8], catalysis [9][10][11] and optical materials [12]. Also Schiff base ligands and some of their complexes have been extensively investigated for more than a century and have been employed in areas that include analytical and bioinorganic chemistry, non-linear optics, fluorescence studies, catalysis and materials chemistry [13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…11). 30 Photoexcitation of the hostguest complex 23·25b resulted in fluorescence exclusively from the square, with higher emission intensity in comparison to the host complex. This is indicative for efficient energy transfer (EnT) from the guest Zn II -salen to the surrounding square (EnT rate constant >10 −10 s −1 ).…”
mentioning
confidence: 99%